Both the unique and repeat regions of the Porphyromonas gingivalis hemagglutinin A are involved in adhesion and invasion of host cells - Bélanger, Myriam (2011)
Porphyromonas gingivalis is one of the major etiologic agents of adult periodontitis and has been associated with cardiovascular diseases. It expresses multiple hemagglutinins that are significant virulence factors that play an important role in bacterial attachment and invasion of host cells. The objective of this study was to determine the impact of P. gingivalis hemagglutinin A (HagA) on the attachment to and invasion of human coronary artery endothelial cells (HCAEC) and gingival epithelial cells (GEC). Bacterial strains expressing the HagA protein (or subunits), including Escherichia coli carrying plasmid pEKS5, E. coli carrying plasmid ST2, and Salmonella enterica serovar Typhimurium with plasmid pNM1.1 were used in this study. The strains were tested for their ability to attach to and invade HCAEC and GEC using antibiotic protection assays. In addition, the unique 5′ N-terminal non-repeated segment of HagA was purified in recombinant form and a monoclonal antibody was created against the polypeptide. The monoclonal antibody against the unique portion of HagA was tested for inhibitory activity in these assays. The attachment of both E. coli strains expressing HagA fragment to host cells was significantly increased compared to their respective controls. However they did not invade GEC or HCAEC. Interestingly, HagA expression in the Salmonella strain increased both adherence to and invasion of HCAEC, which may be due to the presence of the entire hagA ORF. A monoclonal antibody against the unique 5′ N-terminal portion of HagA reduced invasion. Further experiments are needed to determine the role of the unique and the repeat segments of P. gingivalis HagA.